2016
DOI: 10.3310/hta20690
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness, acceptability and cost-effectiveness of psychosocial interventions for maltreated children and adolescents: an evidence synthesis

Abstract: BackgroundChild maltreatment is a substantial social problem that affects large numbers of children and young people in the UK, resulting in a range of significant short- and long-term psychosocial problems.ObjectivesTo synthesise evidence of the effectiveness, cost-effectiveness and acceptability of interventions addressing the adverse consequences of child maltreatment.Study designFor effectiveness, we included any controlled study. Other study designs were considered for economic decision modelling. For acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 548 publications
(2,156 reference statements)
2
40
0
Order By: Relevance
“…Cognitive Behavioural Therapy. Seven reviews investigated CBT for a range of ACE populations [15][16][17][18][19][20][21]. The most substantive results come from Macdonald et al's review, which found that CBT improved mental health outcomes for people who had experienced abuse or neglect [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive Behavioural Therapy. Seven reviews investigated CBT for a range of ACE populations [15][16][17][18][19][20][21]. The most substantive results come from Macdonald et al's review, which found that CBT improved mental health outcomes for people who had experienced abuse or neglect [19].…”
Section: Resultsmentioning
confidence: 99%
“…Other psychological therapies. A range of other psychological therapies, such as brief motivational interviewing, family therapy and psychodynamic psychotherapy, were evaluated in six reviews [15,18,19,[21][22][23]. The findings do not provide strong evidence of effectiveness, although the interventions are heterogeneous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we warn against too much optimism about the effects of interventions for foster children and foster families. There are several overview studies indicating the limited effects of interventions aimed at foster children and foster parents (Benesh & Cui, 2016;Dorsey et al, 2008;Macdonald et al, 2016;Rork & McNeil, 2011;Turner, Macdonald, & Dennis, 2007). It is therefore important to further develop and examine new interventions for foster care (Dorsey et al, 2008;Hambrick, Oppenheim-Weller, N'zi, & Taussig, 2016).…”
Section: Directions For Improvements In Foster Carementioning
confidence: 99%
“…These include the fact that much of the research on the manuals’ effectiveness has been carried out in the United States, generally on single forms of maltreatment. A recent systematic review (Macdonald et al., ) concluded that ‘it is difficult to draw very firm conclusions about which interventions are effective for which children, with what maltreatment, in what circumstances’ and ‘Most children experience more than one form of maltreatment, and there is growing recognition of the need to better take into account children's profiles of maltreatment in order to improve policy and practice’ ( pp. vii and 38 ) .…”
Section: Nice Guideline: Strengths Limitations and Possible Solutionsmentioning
confidence: 99%